Analysing the DNA integrity in hypo-osmotic swelling test types of tail curling and assessing if HOS type “B” outweighs the rest - Yuvaraj, Swathy; G., Manjula; Vembu, Radha; Reddy, Sanjeeva; Pandurangi, Monna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: One of the important steps in ICSI is to select a sperm with good DNA content to have a successful out-come. In case of complete asthenozoospermia the aim is to select a viable sperm using the hypo-osmotic swelling test. There has been lot of debate regarding type of tail curling and their DNA integrity. This study aimed to analyze DNA integrity among different hypo-osmotic swelling (HOS) types of tail curling and determine whether HOS type B has superior DNA quality compared to other types. Methods: A total of 43 semen samples were collected from patients who attend a tertiary care centre in Chennai. The samples were subjected to HOS testing, followed by DNA integrity assessment using acridine orange staining. Results: The study found that sperm with HOS type B tail curling exhibited significantly lower DNA fragmentation (24.6%) compared to HOS type A (97.7%) and other types (61.9%), suggesting that HOS type B sperm possess better DNA integrity. Conclusions: These findings propose that selecting HOS type B sperm in cases of asthenozoospermia for intracytoplasmic sperm injection (ICSI) could enhance outcomes, as this method is cost-effective and identifies sperm with good DNA content.